Book Reviews (The Muslim world, 2002)
Book reviewed in this article: De Medieval Islamic Controversy Between Philosophy and Orthodoxy: Ijmā and Ta'w?l in The Conflict Between Al-Ghazāl? and Ibn Rushd in Islamic Philosophy and Theology, Texts and Studies, Volume 3: Iysa A. Bello Beauty in Arabic Culture by Doris Behrens-Abouseif The Making of an Egyptian Arab Nationalist: The Early Years of Azzam Pasha, 1893–1936 by Ralph Coury Civil Islam: Muslims and Democratization in Indonesia by Robert W. Hefner